A genealogy of queerbaiting: Legal codes, production codes, 'bury your gays' and 'The 100 mess'. (1st June 2018) - Bridges, Elizabeth
Contemporary queerbaiting is a historically situated phenomenon that in significant ways parallels reactions to nineteenth-century legal-medical discourse on the nature of homosexuality, and the subsequent punishment of it through enforcement of sodomy laws and/or blackmail against (primarily) gay men. In the twentieth century, movie and TV morality codes enacted a parallel dynamic of enforcement and punishment, at first with the banning of any mention of homosexuality altogether. Later, as codes relaxed and homosexuality became visible on-screen, film and TV moved from silencing to punishing, with the tendency kill queer characters or otherwise present them as miserable and morally compromised. The 'bury your gays' (BYG) trope, a phenomenon adjacent to queerbaiting, developed out of these decades of the enforcement-punishment dynamic and continues even decades after the codes lost sway. In contemporary television, where queerness is no longer entirely taboo, queerbaiting often gives way to canon queer characters, who are still killed at vastly disproportionate rates compared with their heterosexual counterparts. The fandom of one such character – Lexa, killed off from the American CW network's series The 100 in March 2016 – brought the dual problems of queerbaiting and BYG into the open via a series of unprecedentedly well-coordinated media actions that have, perhaps, led TV writers to rethink how they present their queer characters in the context of socially aware, interactive audiences.